Knowledge and Attitude regarding menstrual cups among young women - Thapa, Tannu; Mary Roy, Susha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Menstruation is cyclic vaginal bleeding that occurs physiologically as a result of the shedding of the endometrium. The maintenance of adequate perineal hygiene during menstruation is very important. One product which is gaining quite a popularity over few years is a flexible, reusable cup that is inserted inside the vagina to collect blood during menstruation known as a menstrual cup. The benefits of a menstrual cup are numerous which include comfort, hygiene, cost-effectiveness and eco-friendliness. The acceptance of menstrual cups among women in India is varied due to personal and sociocultural factors. The objective of this study was to assess the knowledge and attitude regarding menstrual cups among young women. Methods: A descriptive study design was adopted for the study. 200 young women were selected using non-probability convenient sampling technique. The study tool was administered to assess the knowledge and attitude regarding menstrual cups. Results: Among 200 young women, 49% of young women had adequate knowledge, 43.5% had moderately adequate knowledge and 7.5% had inadequate knowledge regarding menstrual cups. 64.5% of young women had neutral attitude, 31% had positive attitude and 4.5% had negative attitude regarding menstrual cups. Conclusions: Though young women are aware of menstrual cups but majority of them are skeptical towards its use. The findings suggests that mass in-depth awareness programmes for nurses and other health professionals should be organised and support groups need to be created to provide adequate information and counselling to the public regarding the use of menstrual cups.